INTERNET’S CONTRIBUTION IN PROMOTION OF MUSIC: संगीत के प्रचार में इन्टरनेट का योगदान - masatkar, Ashih (International Journal of Research -GRANTHAALAYAH, 2015)
In modern times, internet has become a medium of propagation that has tied the whole world into one thread. In the common language, the Internet is called the Network of Networks, on this network information is exchanged as electrical signals. Internet is a means of sharing information. Assistance of any person to diagnose a problem is possible through it. Through very fast, we can send information from one place to another. आधुनिक समय में इन्टरनेंट एक ऐसा प्रचार-प्रसार का माध्यम बना हुआ है जिसने संपूर्ण विश्व को एक सूत्र में बांध दिया है। सामान्य भाषा में इंटरनेट को नेटवर्क आॅफ नेटवक्र्स कहा जाता है इस नेटवर्क पर सूचनाओं का आदान - प्रदान विद्युत संकेतों के रूप में किया जाता है। इंटरनेट सूचनाओं का आदान - प्रदान करने का साधन है। किसी समस्या के निदान हेतु कहीं भी किसी भी व्यक्ति की सहायता इसके माध्यम से संभव है। अति तीव्र माध्यम से हम जानकारियाँ एक स्थान से दूसरे स्थान तक भेज सकते है।